Percampuran kod bahasa di dalam filem: satu kajian kualitatif terhadap filem J Revolusi (2017) / Mohd Syuhaidi Abu Bakar and Nor Audra Dayana Dahlan - Abu Bakar, Mohd Syuhaidi; Dahlan, Nor Audra Dayana (2018)
The responsibility for empowering Malay is not only held by the Dewan Bahasa dan Pustaka (DBP) but also lies within the practitioners of film and television industry in Malaysia. However, there are still many films in Malaysia that still practice the Mixing of the Language Code in their dialogue. This study was conducted qualitatively using Text Analysis and Coding Book to see the use of mixed code mixing and internal code mixing in the J Revolusi movie (2017). The film was chosen because of the warm welcome and the number of viewers who paid attention to the movie. The findings show that there are 161 uses of mixed language code and 35 uses of internal language code mixes exist in the movie. The findings also found that the use of mixed language code was influenced by the social factors of the speakers.